Management of the Incidence of Asphyxia in Newborns - Indrawati Indrawati; Farida Kartini; Wantonoro Wantonoro (Syntax Corporation Indonesia, 2023)
This research is a Scoping Review research. This study aims to map research on the Management of Asphyxia in Newborns. The research method used is to adapt the Prisma-ScR framework. The database used by Pubmed, Sciendirect and Goegle Scholar, then carried out a Critical Appraisal and reviewed using the Joana Brigs checklist instrument from the Joana Brigs Institute (JBI). Results: based on the search results of 315 articles, pubmad 115, sciencdirect 85 articles and google scolar 75 articles, then after screening there were 8 articles that met the inclusion criteria. This review raises two sub-themes, namely the causes of asphyxia and the treatment of asphyxia in newborns. The results of the study show that asphyxia can be treated with resuscitation measures and by increasing the knowledge of midwives in resuscitation, the quality and skills of midwives in resuscitating newborns.